1986
DOI: 10.1080/00986448608911802
|View full text |Cite
|
Sign up to set email alerts
|

Gasification of Coal Chars With Carbon Dioxide and Oxygen

Abstract: The effect of temperature and gaseous compositions on the reactivities of coal derived chars is studied. Experimental data for gasification with CO, are correlated with a Langmuir-Hinselwood type kinetic expression, the inhibition effects of CO are quantified and the temperature dependence of all kinetic constants is presented. A first order expression is used to correlate the reaction rate data during gasification with 0,. Preexponential factors and activation energies for this reaction are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Considering char gasification as the rate-determining step in the overall gasification process, a voluminous amount of research has been carried out to understand char gasification mechanisms. However, the overall kinetics of heterogeneous char gasification varies with different gasifying agents (e.g., H 2 O, CO 2 , and O 2 ) depending on the total available surface area and the number of active sites available per unit surface area per unit time. However, in-depth knowledge on char reactivity is an essential requirement as the char reactivity also depends on the change in the char structure with gasification, alkali and alkaline earth metallic (AAEM) constituents, and porosity. , Studies done on the gasification of low-rank fuel to date have confirmed that the change in the char structure significantly affects char reactivity. Also, the presence of the AAEM species in low-rank coal affects the char structure and reactivity simultaneously. The char gasification process is associated with three complex steps: chemisorption on the active sites present on the char pore surface, surface diffusion of reactive intermediates, and desorption of gasification products from reactive sites. However, not all active sites available for chemisorption at any instant/any conversion level need to be responsible for forming any single key product. , Also, the increase of active sites on the char surface is not essential to increase the yield of the more desired product.…”
Section: Introductionmentioning
confidence: 99%
“…Considering char gasification as the rate-determining step in the overall gasification process, a voluminous amount of research has been carried out to understand char gasification mechanisms. However, the overall kinetics of heterogeneous char gasification varies with different gasifying agents (e.g., H 2 O, CO 2 , and O 2 ) depending on the total available surface area and the number of active sites available per unit surface area per unit time. However, in-depth knowledge on char reactivity is an essential requirement as the char reactivity also depends on the change in the char structure with gasification, alkali and alkaline earth metallic (AAEM) constituents, and porosity. , Studies done on the gasification of low-rank fuel to date have confirmed that the change in the char structure significantly affects char reactivity. Also, the presence of the AAEM species in low-rank coal affects the char structure and reactivity simultaneously. The char gasification process is associated with three complex steps: chemisorption on the active sites present on the char pore surface, surface diffusion of reactive intermediates, and desorption of gasification products from reactive sites. However, not all active sites available for chemisorption at any instant/any conversion level need to be responsible for forming any single key product. , Also, the increase of active sites on the char surface is not essential to increase the yield of the more desired product.…”
Section: Introductionmentioning
confidence: 99%